The Right-sided Aortic Arch in Children with Oesophageal Atresia and Tracheo-oesophageal Fistula - Wood, J.A.; Carachi, R. (European Journal of Pediatric Surgery, 2012)
Aim A right-sided aortic arch (RAA) occurs in around 5% of patients with oesophageal atresia and tracheo-oesophageal fistula (OA/TOF). This anatomical variation can complicate the operative management of these patients, as it is often not diagnosed preoperatively but only discovered at thoracotomy, and it remains unproven as to whether a right or left thoracotomy is the best operative approach. This retrospective study aimed to determine the prevalence of RAA in OA/TOF, review the accuracy of preoperative investigations, and investigate the best operative approach, by reviewing the literature and our own patient series.Methods The case notes of all infants with OA/TOF over a 15 year period (1994–2008) were retrospectively analysed to identify those with a RAA. Birth weight, gestational age, associated anomalies, preoperative investigations, surgical management, postoperative complications and long-term prognosis were all extracted.Main Results A total of 107 case notes of OA/TOF infants were reviewed, identifying 4 with a RAA. Preoperative echocardiography was performed in all of the 4 RAA infants, but RAA was only identified in one. All 4 infants were managed surgically via a right thoracotomy, regardless of the echocardiography result, with primary anastomosis achieved successfully in all. A laryngeal cleft repair was performed in 1 infant due to an interarytenoid cleft. Laparoscopic fundoplication was performed in 1 patient, because of severe gastro-oesophageal reflux. There were no postoperative anastomotic leaks, bleeding, or deaths in this group.Conclusion In our study, the incidence of RAA in OA/TOF was 3.7%. Preoperative echocardiography identified the RAA in only 1 of 4 cases. However, echocardiography was helpful for diagnosing other cardiac anomalies, which might have potentially affected the management of these patients. Previous studies have cited the operative difficulties associated with RAA and OA/TOF. However, in this series of 4 infants, primary anastomosis was achieved via conventional right thoracotomy without complication, and with no effect on outcome or prognosis. Therefore, we conclude that, where possible, a conventional right-sided thoracotomy should be performed in OA/TOF patients with a RAA.
Keywords: right-sided aortic arch; oesophageal atresia; tracheo-oesophageal fistula